Parenting: Educational Parenting Patterns in Muslim Families at Ponpes Modern Gatra, Kohod Village, Pakuhaji District, Tangerang Regency - Muhamad Wira Syaprudin; Dul Jalil (IRDH International Journal of Social Sciences & Humanities, 2025)
This activity aims to enhance the understanding of the parents of students regarding the importance of family education as the main foundation for character development in children. The methods used include interactive seminars, group discussions, and Q&A sessions to provide both theoretical and practical knowledge. The results of the seminar show that participants gained new insights into the role of parents in educating children with an Islamic approach, the importance of healthy communication, and the synergy between home and pesantren. The impact of this activity includes increased awareness among parents, the formation of a commitment to improve parenting patterns, and readiness to cooperate with the pesantren. However, there are obstacles such as limited time for parents, low levels of Islamic parenting literacy, inconsistency in practices at home, and a less supportive social environment. Therefore, follow-up actions in the form of forming parenting communities, periodic training, collaboration with Islamic boarding schools, and practical assistance at home are proposed as follow-up strategies. With consistency and support from all parties, it is hoped that Muslim families can raise a generation of faithful, ethical individuals ready to face the challenges of the times